An Innovative Approach for Highly Selective Direct Conversion of CO2 into Propanol using C2H4 and H2. Issue 9 (10th July 2014) - Ahlers, Stefan J.; Bentrup, Ursula; Linke, David; Kondratenko, Evgenii V.
Abstract Multifunctional catalysts are developed for converting CO2 with C2H4 and H2 into propanol. Au nanoparticles (NP) supported on TiO2 are found to facilitate this reaction. The activity and selectivity strongly depend on NP size, which can be tuned by the method of Au deposition and by promoting with K. The promoter improves the selectivity to propanol. Under optimized reaction conditions (2 MPa, 473 K, and CO2/H2/C2H4=1:1:1), CO2 is continuously converted into propanol with a near‐to‐100 % selectivity. Catalytic tests as well as mechanistic studies by in situ FTIR and temporal analysis of products with isotopic tracers allow the overall reaction scheme to be determined. Propanol is formed through a sequence of reactions starting with reverse water–gas shift to reduce CO2 to CO, which is further consumed in the hydroformylation of ethylene to propanal. The latter is finally hydrogenated to propanol, while propanol hydrogenation to propane is suppressed.